Analysis of students error in completing hots questions on fruction additional and subtraction operations class V SDN Karangtengah I - Wulandari, Linda; Trisniawati, Trisniawati; Rhosyida, Nelly; Murniningsih, Murniningsih (International Journal of Insights for Mathematics Teaching, 2023)
This study aims to 1) to describe the mistakes made by fifth graders at SDN Karangtengah I in solving HOTS questions on the addition and subtraction of fractions in grade V. 2) To describe the factors that caused fifth graders at SDN Karangtengah I to make mistakes in solve HOTS questions on the material of addition and subtraction of fractions in class V. This type of research is descriptive qualitative, with data sources from students and teachers of class V SDN Karangtengah I. Data collection techniques use written tests, interviews, observations and documentation. While the data analysis technique used is the analysis of the Miles and Huberman model which consists of data collection, data reduction, data display, and drawing conclusions. The results of this study indicate that 1) in solving the HOTS questions for adding and subtracting fractions, the fifth-grade students of SDN Karangtengah I make errors in encoding error with a percentage of 41.94 percent, process skill errors with a percentage of 37.9 percent, transformation errors with a percentage of 13, 71 percent, conprehension errors with a percentage of 4.84 percent, and reading errors with a percentage of 1.61 percent. 2) The factors that cause students to make mistakes in solving HOTS questions on addition and subtraction material are 2 factors, namely external factors and internal factors. The external factors that cause students to make mistakes because the learning process does not get used to the use of HOTS questions. Furthermore, the internal factors that cause students to make mistakes are a) the encoding error indicator is that students do not know the next step after carrying out the calculation process and students do not know how to conclude answers; b) the process skill error indicator is that students' numeracy skills are low, students do not know the concepts of fractional arithmetic operations and porogapit; c) the transformation error indicator is that students cannot determine arithmetic operations; d) on the comprehension error indicator, students have difficulty in writing down the information contained in the questions, students do not write down the information contained in the questions and students are in a hurry to take the test; e) the reading error indicator is that students are not careful in reading the questions and students are not able to understand the keywords or sentences in the questions; and the most common internal factor is the intellectual ability of students and students experience errors in the previous stage.